ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Ainiyah, Rahmatul; Wiryaningtyas, Dwi Perwitasari; Ariyantiningsih, Febri (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The research objective is to determine the Analysis of Factors Influencing Stock Prices with Capital Structure as Intervening Variables in Property and Real Estate Companies Listed on the Indonesia Stock Exchange (IDX). In this study the sampling technique used was purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that Net profit margin has a positive and significant effect on capital structure, Current ratio has a positive and significant effect on Capital structure, Net profit margin has a positive and significant effect on stock prices, Current ratio has a positive effect and significant effect on stock prices, capital structure has a negative but significant effect on stock prices, net profit margin has a significant negative effect on stock prices through capital structure, current ratio has no significant negative effect on stock prices through capital structure.